2005
DOI: 10.1159/000083553
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of the Effect of Extracorporeal Magnetic Stimulation on Urinary Incontinence after Radical Prostatectomy: A Pilot Study

Abstract: Introduction: Radical prostatectomy is a common procedure for the treatment of clinically localized prostate cancer. However, urinary incontinence is a significant potential source of morbidity following surgery. Extracorporeal magnetic stimulation (ExMS) is a new technology used for pelvic muscle strengthening in the treatment of stress urinary incontinence. We investigated the clinical effects of ExMS on urinary incontinence after retropubic radical prostatectomy. Patients and Methods: Ten patients who had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(16 reference statements)
0
7
0
1
Order By: Relevance
“…Many efforts, including neuromodulation, have been made to achieve early urinary continence. Yokoyama et al reported that extracorporeal magnetic stimulation improved continence in 60% of patients with PPI [9, 10]. On the other hand, two randomized control studies failed to show an additional effect of neuromodulation for PPI compared with PME alone [7, 8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts, including neuromodulation, have been made to achieve early urinary continence. Yokoyama et al reported that extracorporeal magnetic stimulation improved continence in 60% of patients with PPI [9, 10]. On the other hand, two randomized control studies failed to show an additional effect of neuromodulation for PPI compared with PME alone [7, 8].…”
Section: Discussionmentioning
confidence: 99%
“…These methods were used to treat postprostatectomy incontinence (PPI) [710]. A certain effect was observed in these studies, while these studies were applied only for patients with urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…It was used “incontinence episodes” from data collected with a 3‐day bladder diary. Men with a 50% or greater reduction in incontinence episodes were considered improvements 14 . The Quality of Life‐Incontinence Impact Questionnaire (IIQ7) was used to assess specific QoL related to incontinence 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Men with a 50% or greater reduction in incontinence episodes were considered improvements. 14 The Quality of Life-Incontinence Impact Questionnaire (IIQ7) was used to assess specific QoL related to incontinence. 15 Higher scores indicate worse incontinence-related QoL.…”
Section: Evaluation Parametersmentioning
confidence: 99%
“…The promising role of ExMS on urinary incontinence after radical prostatectomy has been recently pinpointed by Yokoyama et al [43] , who found effi cacy of ExMS therapy from subjective and objective points of view, even if their series was small and a control group was missing. They then suggest the need of properly designed placebo-controlled studies to further determine the efficacy of this treatment, how long its benefi ts last and whether maintenance is necessary.…”
Section: Rehabilitation Therapy and Post-prostatectomy Urinary Incontmentioning
confidence: 99%